Researching and Teaching Second Language Speech Acts in the Chinese Context - Lee, Cynthia (Springer Singapore, 2018)
This book contributes to the literature of interlanguage pragmatics by building an interface between researching and teaching speech acts in the Chinese context. It is written for researchers, language educators, classroom teachers and readers who are interested in interlanguage pragmatics research, acquisition and teaching, with particular reference to speech acts performed by Chinese learners of English, and their relationships with the learners' first language and cultural concepts. It provides a more advanced understanding of the production and development of speech acts of Chinese learners of English from the cross-linguistic, cross-cultural, L1 and L2 developmental perspectives, drawing on relevant second language acquisition theoretical frameworks. It also recommends research-informed pedagogies that are applicable to other learners of English.